The Application of Virtual Reality for Vocational Skills of Individuals with Autism Spectrum Disorder: A Systematic Review - Sarri, Kyriaki; Syriopoulou- Delli, Christine; Gkiolnta, Eleni; Zygopoulou, Maria (Eximia, 2022)
Employment is one of the major problems faced by individuals with autism spectrum disorder (ASD) during their transition to independent living. Unemployment and underemployment are very common in this population, indicating a gap in vocational rehabilitation. Effective vocational instruction is therefore very important for individuals with ASD, and virtual reality (VR) appears to be a promising technology for providing adolescents and young adults with ASD with the skills needed to access competitive employment. In a systematic literature review, eight studies reporting VR applications for vocational skills were identified, involving 345 participants with ASD, with or without comorbid diagnoses. The results indicate that VR intervention benefits adolescents and young adults with ASD in enhancement of their interviewing skills for work positions, but further research is urgently needed, which should focus on the maintenance and generalization of the acquired skills.